Chemical Composition, Antioxidant and Anti-tumor Activities of the Aerial Parts of Cometes abyssinica R.Br. ex Wall - Abdelgawad, Ahmed AM (Indian Journal of Pharmaceutical Education and Research, 2023)
An in vitro bioassay-guide revealed that the methanolic extract of the aerial parts of Cometes abyssinica had considerable inhibitory activity against colon (HCT-116) and hepatocellular (HepG2) carcinoma cell lines with IC50 24.4 and 29.9 μg/mL, respectively, compared to the drug reference Cisplatin. On the other hand, all studied extracts exhibited weak antioxidant activities using the DPPH scavenging assay with IC50 values between 543-826.4 μg/mL. Phytochemical investigation of the methanol and ethyl acetate extracts of C. abyssinica led to the isolation of five flavonoid compounds: Formononetin 1, Daidzein 2, Eriodictyol 3, Taxifolin 4, and kaempferitrin 5. The chemical structure of the isolated compounds was identified based on their physicochemical and spectroscopic analyses.
Keywords: Cometes abyssinica; Aerial parts; Chemical constituents; Flavonoids; Antioxidant activity; Antitumor activity